English public opinion and the American Civil War - Campbell, Duncan A., 1968- (Royal Historical Society studies in history. New series., 2003)
English opinion on the American Civil War was not a straightforward division between progression on the side of the Union and reaction on the side of the Confederacy. Rather, it was affected by attitudes of the public to many issues: slavery, neutral rights, democracy, republicanism, trade and propaganda. The evidence gathered here offers a new interpretation of the subject, showing that most people in England were suspicious of both sides in the conflict, and that even those who did take sides did not consist entirely of any one particular social or political group.